Mathematical and Statistics Anxiety: Educational, Social, Developmental and Cognitive Perspectives - Irene Cristina Mammarella; Denes Szucs; Erin Anne Maloney; Carlo Tomasetto; Caterina Primi; Kinga Morsanyi (Frontiers Media SA, 2017)
Mathematical anxiety is a feeling of tension, apprehension or fear which arises when a person is faced with mathematical content. The negative consequences of mathematical anxiety are well-documented. Students with high levels of mathematical anxiety might underperform in important test situations, they tend to hold negative attitudes towards mathematics, and they are likely to opt out of elective mathematics courses, which also affects their career opportunities. Although at the university level many students do not continue to study mathematics, social science students are confronted with the fact that their disciplines involve learning about statistics - another potential source of anxiety for students who are uncomfortable with dealing with numerical content. Research on mathematical anxiety is a truly interdisciplinary field with contributions from educational, developmental, cognitive, social and neuroscience researchers. The current collection of papers demonstrates the diversity of the field, offering both new empirical contributions and reviews of existing studies. The contributors also outline future directions for this line of research.
English
Keywords: Measurement; Statistics anxiety; Anxiety specificity; developmental change; emotional factors; Mathematical anxiety; mathematics performance; gender differences